Mexican youth on AI: Their visions of tomorrow: Jóvenes mexicanos ante la IA: sus visiones del mañana - Téllez Tula, Ángel; Asino, Tutaleni; Gutiérrez Gutiérrez, Benjamín; Mendoza Zaragoza, Norma Elena; Herrera Corona, Laura (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2026)
Artificial Intelligence (AI) has become increasingly embedded in the daily lives of young people, yet its educational, social, and ethical implications remain insufficiently explored in secondary school contexts in Mexico. This study examines the perceptions, levels of familiarity, frequency of use, and educational expectations regarding AI among Generation Z students enrolled in technical junior high schools. A mixed-methods exploratory design with quantitative dominance was employed. Data were collected through an online questionnaire administered to 560 students aged 11 to 15, combining closed-ended items with open-ended questions. Quantitative data were analyzed descriptively to identify general trends, while qualitative responses were examined through thematic analysis to capture interpretative categories related to students’ views on AI. The findings reveal widespread exposure to AI technologies, accompanied by predominantly functional rather than conceptual understanding. Students expressed neutral or ambivalent perceptions regarding AI’s impact on Mexico’s future and employment, alongside frequent, often unreflective, use of AI-based applications. Despite these uncertainties, a majority demonstrated openness toward AI-related educational opportunities and identified education as the sector most likely to benefit from AI implementation. Qualitative results further revealed a dual discourse that simultaneously recognizes AI’s usefulness and expresses ethical concerns related to dependency, creativity, and academic integrity. The study highlights the need for educational strategies that move beyond incidental interaction with AI toward structured, critical, and ethically grounded AI literacy. These findings contribute empirical evidence to ongoing debates on the responsible integration of artificial intelligence in secondary education within the Mexican context.